Governance subsequent to the merger of a province: Canon 581 - McDermott, Rose (CLSA advisory opinions, 2001-2005, 2003)
In a community of two provinces, if the small province is absorbed into the much larger province (thirty-two members merging with three hundred members), is this now-combined entity required to hold new elections for a new provincial and her council?